1995
DOI: 10.1002/jcu.1870230403
|View full text |Cite
|
Sign up to set email alerts
|

Color Doppler sonography: Anatomic and physiologic assessment of the thyroid

Abstract: The purpose of this study was to assess the potential application of color Doppler sonography in thyroid imaging. Thyroid nodules and other thyroid pathology detected by color Doppler ultrasound and nuclear scintigraphy were compared in 115 patients. The majority of "cold" nodules demonstrated a peripheral rim of color flow and no internal color flow with color Doppler sonography. A large number of "hot" nodules demonstrated internal color flow. Color Doppler sonography was helpful in delineating nodules in ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0
7

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 7 publications
3
43
0
7
Order By: Relevance
“…Thus, in this study, the vascular patterns of FC evaluated by power Doppler sonography could be of value in differentiating malignant FC from benign FA. In agreement with previous studies [2,6,8,11], the color flow pattern of benign nodules demonstrated a peripheral rim of color flow or no color flow. This appearance is likely related to compression of normal thyroid tissue due to growth of the adenoma or adenomatous tissues.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, in this study, the vascular patterns of FC evaluated by power Doppler sonography could be of value in differentiating malignant FC from benign FA. In agreement with previous studies [2,6,8,11], the color flow pattern of benign nodules demonstrated a peripheral rim of color flow or no color flow. This appearance is likely related to compression of normal thyroid tissue due to growth of the adenoma or adenomatous tissues.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, high resolution pulsed and color Doppler US (CD) are widely used as noninvasive procedures that can easily obtain interesting data about the vascularity of parenchymatous structures. Recent investigators have indicated that the contemporary means of evaluating morphology and vascular structures may have an important role in the differential diagnosis of benign and malignant tumor [8][9][10][11][12][13][14]. But, to date, the application of power Doppler US to thyroid follicular tumor analysis has not been demonstrated as having definite clinical usefulness.…”
mentioning
confidence: 99%
“…The mean EDV was 4.5 cm/sec (range 1-15) in the melanoma group and 7.1 cm/sec (range [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] in the metastases group (p=0.11). The mean PSV was 12.9 cm/sec (range 3-36) in the melanoma group and 19.1 cm/sec (range 5-57) in the metastases group (p=0.25).…”
Section: Resultsmentioning
confidence: 99%
“…Many diagnoses, such as testicular torsion, orchitis, epididymitis (11), thyroiditis (12), lymphadenitis versus metastatic disease in lymph nodes (13) and synovitis (14), are made solely on subjective color Doppler estimations. Although tumors can be characterized as being hypo-or hyper-vascular, CFM is not specific and additional imaging or histologic evaluation is usually needed (15,16). Tumors have also been evaluated by CFM characterizations, such as the absence of vascularization, presence of peripheral vascularization and presence of central vascularization, by means of methods similar to the one used in the current study (17).…”
Section: Discussionmentioning
confidence: 99%
“…If a solitary adenoma is seen in the case of a hyperthyroid functional state, the probability that this represents carcinoma is extremely low. Regressive thyroid nodules, however, usually only show peripheral and not central vascularization [21].…”
Section: Conventional B-mode Ultrasoundmentioning
confidence: 99%